PEMBERDAYAAN KELOMPOK NELAYAN MELALUI PROGRAM SENTRA KELAUTAN DAN PERIKANAN TERPADU (SKPT) DI KABUPATEN MALUKU BARAT DAYA - Mutiar Fitri Dewi; Frans Simon Dadiara (ipdn, 2022)
Indonesia's fisheries potential has an essential and strategic role for the national development since it influences economic, security, ecological and social aspects. With this important role, it is assumed that the living standard of Indonesia’s fishermen improved. However, based on the data from the Ministry of Maritime Affairs (2018), most Indonesia’s fishermen still live within the poverty line. This current study aims at describing the implementation of fishermen group empowerment through integrated marine and fisheries center program in Maluku Barat Daya District. The data of this study are gathered through direct observation, in-depth interview and documentation study. Then they are analyzed based on Empowerment theory by Mardikanto and Soebiato (2017). The study’s result show that the empowerment emerged in three aspects namely human, business, and institutional development. It is also found that the empowerment process is still not optimal due to several obstacles namely lack of awareness of fishermen group, characteristics of the archipelago, and inadequate communication network. To overcome these, the Fishery Department has made efforts such as giving training, distributing fishing gears, and establishing certain fishermen groups. Suggestions given by the authors are giving self-awareness and work ethics socialization, cooperating with the heads of village, and issuing local government regulation regarding fishery. Keywords: Empowerment, Fishermen Group, Integrated Marine and Fisheries Center Program